The relationship between office environment and employees productivity at Pejabat Daerah Dungun / Nurul Izwani Mohamad Mahyidin - Mohamad Mahyidin, Nurul Izwani (Faculty of Business and Management, 2017)
The workplace environment plays a crucial role for the employees. Nowadays employees may have a large number working alternatives, and then the environment in workplace becomes a critical factor for accepting and/or keeping the jobs. The quality of environment in workplace may simply lead the employee's productivity. This paper presents the analysis of working environment at Pejabat Daerah Dungun and examines the relationship between the office environment and employee's productivity. The scope of this study was the staff at Pejabat Daerah Dungun. The data of this study were gathered through the distribution of questionnaires using convenience sampling technique. The total of the questionnaires used in this study were 41 questionnaires and give by face to face to the respondents and collected immediately. The data gathered were analyzed by using the Statistical Package for Social Science (SPSS) software version 20. The result of the study has been generated and tabulated and based on the findings, the researcher has successfully achieved the objectives, and the tested hypothesis of this study. Keyword Workplace Environment, Employees' Productivity.